MBN implementation in Barangay Pantig - Bautista, Victoria A. (1999)
Barangay Pantig was one of the pioneers in installing the MBN information system. Despite this edge, the barangay was not able to phase in the other requisites of successful project implementation (SAPIME or situation analysis, planning, implementation, and monitoring and evaluation). Inadequate social preparation of the community for the entry of the MBN intervention was a major flaw. This was worsened by the barangay captain's top-down leadership style, which isolated him and his reliable workers from the local populace. Although the barangay leadership has produced initial success, these feats could hardly be sustained because the community lacks a sense of ownership of the activities in the locality.
Keywords: Basic needs -- Case studies -- Barangay Pantig; Minimum Basic Needs (MBN); Minimum Basic Needs Information System; Social Reform Agenda (SRA); Leadership; Situation Analysis, Planning, Implementation, and Monitoring and Evaluation (SAPIME)